Pengembangan Kompetensi Profesional Guru Pendidikan Agama Islam Dalam Meningkatkan Praktik Pengajaran - Reksiana Reksiana (Prodi Pendidikan Keagamaan Islam, 2026)
The development of professional competence among Islamic Religious Education (PAI) teachers is a strategic concern in improving the quality of school-based teaching and learning. This study aims to analyze the process, strategies, and impact of professional competence development among PAI teachers at SMP Negeri 6 Tangerang Selatan, with attention to the role of school leadership and contributing or hindering factors. Employing a qualitative phenomenological approach, data were collected through non-participant observation, in-depth interviews, and document analysis involving one school principal, two PAI teachers, and three students. Data were analyzed using Saldana's coding model through first-cycle coding, second-cycle coding, and thematic development. The findings reveal three primary pathways of competence development: (1) formal institutional programs through government-facilitated training; (2) collegial learning through the Subject Teacher Forum (MGMP); and (3) self-directed digital learning initiatives. These pathways are mutually reinforcing in strengthening subject-matter expertise, pedagogical creativity, and technology integration. The school principal plays a pivotal role in facilitating a professional learning culture. The study also identifies key challenges, including digital literacy gaps between senior and junior teachers, limited sustained engagement in continuing professional development (CPD), and heavy administrative burdens. These findings contribute to the development of a differentiated, contextual, and sustainable CPD model for PAI teachers.